1984
DOI: 10.1002/bit.260260824
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of intracellular accumulation of poly‐β‐hydroxybutyrate (PHB) in individual cells of Alcaligenes eutrophus H16 by flow cytometry

Abstract: Poly-beta-hydroxybutyrate (PHB) accumulates in individual cells of Alcaligenes eutrophus in the form of refractile bodies which alter the light-scattering properties of individual cells. Flow cytometry has been applied to measure the distributions of single-cell light-scattering intensity in Alc. eutrophus populations during batch cultivation of the organism. These measurements clearly identify heterogeneities in the inoculum which influence the lag interval prior to beginning of exponential growth. Light-scat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(42 citation statements)
references
References 26 publications
0
40
0
2
Order By: Relevance
“…Cultures of both PHB-negative mutants had yielded optical densities of about 350 Klett units and remained at this value, whereas the optical density of strain H16 increased further. This is due to the accumulation of PHB, which is stored as refractile grana, causing a further increase of the light scattering of the cells and thereby of the optical density of the solution (Schlegel et al, 1970b;Srienc et al, 1984). After 12 h cultivation, the wild-type had reached an optical density of about 570 Klett units.…”
Section: Resultsmentioning
confidence: 99%
“…Cultures of both PHB-negative mutants had yielded optical densities of about 350 Klett units and remained at this value, whereas the optical density of strain H16 increased further. This is due to the accumulation of PHB, which is stored as refractile grana, causing a further increase of the light scattering of the cells and thereby of the optical density of the solution (Schlegel et al, 1970b;Srienc et al, 1984). After 12 h cultivation, the wild-type had reached an optical density of about 570 Klett units.…”
Section: Resultsmentioning
confidence: 99%
“…The first studies applying flow cytometry to bacteria dealt with the description of the macromolecular composition of bacterial cells during the growth cycle: changes in DNA were found to correlate with the fluorescence of the probes used (see below), changes in protein content with changes in bacterial size (Allman et al, 1990) and changes in the scatter of light by the cells have been found to reflect changes in bacterial size (Allman et al, 1990) or the accumulation of reserve polymers such as poly-ß-hydroxybutirate (e.g. Srienc et al, 1984).…”
Section: Bacteria and Flow Cytometrymentioning
confidence: 99%
“…The amount of bacterial scattered light is a complex function of cell size, internal structure, particle orientation, refractive indexes of the particle and of the medium, etc. Cellular inclusions like PHB (Srienc et al, 1984), sulfur (E.O.Casamayor and J.M. Gasol, unpubl.…”
Section: Bacterial Detection By Light Scatteringmentioning
confidence: 99%
“…Poly(hydroxybutyrate) (PHB) is a wellknown member in the PHAs family. PHB has received considerable attention because of its renewability and biocompostability under both aerobic and anaerobic conditions (Srienc, Arnold, & Bailey, 1984). However, it has not been widely applied yet as a commodity material due to the high price, poor processability and brittleness (Masayuki & Keiichi, 2006;Pan & Inoue, 2009).…”
Section: Introductionmentioning
confidence: 99%